The Contribution of Village Fund Management for Creating More Prosperous Society: an Empirical Study at Central Java - Susilowati, Nurdian; Mahmud, Amir; Rachmadani, Wulan Suci; Lestari, Sari; Tusyanah, Tusyanah (Universitas Pendidikan Indonesia, 2020)
The purposes of this research are first to explain the readiness of villages in managing the village fund. Second, to generate a mapping of priorities for the use of village fund. Third, to analyze the implementations of financial management of the village fund. This research uses a case study. The main data sources of this research are the village chiefs, village secretaries, village treasurers, and society in Central Java. The results show the villages are ready to manage the village fund originating from the national budget. The village fund is used to finance physical and non-physical development and empower the society. The implementation of the use of the village fund have been by certain procedures and can be justified so that transparency and accountability can be realized well. The business activities of Village-Owned Enterprises originating from the village fund have proven to be able to move the economy of the village community forward